'One has to take leave as much as possible of one's own standards and values': Improving and measuring historical empathy and perspective reconstruction. Issue 1 (30th April 2019) - Wilschut, Arie; Schiphorst, Koen
Historical empathy or perspective taking has been a bone of contention in studies on history teaching, and the concept remains ill-defined. This may have been caused by a lack of theoretical reflection, as well as by the application of diverse research methods: a more cognitive or 'rational' explanation of the concept has often been substantiated by quantitative methods, while the more affective dimension has regularly been explored by qualitative methods. In this contribution, we trace some theoretical backgrounds of 'empathy' in historical theory as well as social psychology. Then we present a mixed-methods study employing a quantitative standardized measure developed in previous research in Germany and the Netherlands, as well as qualitative measurements. Results suggest that while, on the one hand, the standardized measure proved to be unreliable, both quantitative and qualitative methods can shed more light on what is going on when students try to take the point of view of historical agents. Based on theory, as well as our explorations, our conclusion is that empathy or perspective taking should be seen as a cognitive operation. We propose to see the reconstruction of historical perspectives as a specific element of historical explanation, not as a separate concept of 'historical empathy' or 'historical perspective taking'.